An arteriovenous malformation as a rare cause of sciatic neuropathy: a case report - Akar, Ezgi; Akgün, Mustafa; Akmil, Mehmet Ufuk (The European Research Journal, 2018)
Sciatica is characterized by pain and discomfort occurring frequently with impingement at the level of spinal nerve along the regions innervated by the sciatic nerve. Compression and irritation of the nerve often occurs with a spinal cause such as lumbar disc hernia or spinal stenosis. Compression of the nerve by an arteriovenous malformation is very rare among the causes leading to nondiscogenic sciatic neuropathy. Herein, we reported our case with clinically and electrophysiologically typical sciatic neuropathy and treated by us surgically. To our knowlodge, cases with arteriovenous malformation -caused sciatica were limited in the literature review. Electromyography should be performed to exclude the nerve compression due to rare causes such as vascular causes which may lead to sciatic neuropathy in patients with sciatic distribution symptoms and signs, after initial negative spine imaging.